Diversidade e taxonomia de leveduras associadas a fitotelmos em áreas de cerrado nos estados do Tocantins e Minas Gerais - Francisca Maria Pinheiro de Sousa (2015)
Phytotelmata are water tanks accumulated in some part of the plant and are used by a range of organisms searching for food resources or as habitat and refuge. Plants that most often form phytotelmata mainly belong to Bromeliaceae family. However, other plants, such as Paepalanthus genus are also capable of forming such structures. The ecology of yeasts associated with phytotelmata is poorly studied. Although studies of yeasts isolated from bromeliad phytotelmataare already developed, researches that include diversity of thesemicroorganisms are still scarce. Most of studies about yeasts associated with these environments are focused on discovery of new species. The aim of this study was to characterize the distribution and diversity of yeasts associated with phytotelmata, in areas of Cerrado in the states of Tocantins and Minas Gerais. A total of 491 yeast isolates were obtained, being 166 from Bromelia karatas phytotelmata and 94 isolates from Encholirium sp., in Aurora do Tocantins; 137 isolates from Paepalanthus bromelioides and 94 isolates from Vrisea minarum in Serra do Cipó. Four yeast species were shared among these phytotelmata, being Cryptococcus laurentii, Cr. nemorosus, Pseudozyma hubeiensis andRhodotorula mucilaginosa. Anomalomyces yakirrae, C. glabrata, C.orthopsilosis, C. orthopsilosis, C. pseudointermedia, Cr. heveanensis, Cr. laurentii, Cr. nemorosus, M. guilliermondii and P. jejuensis presented higher frequency of isolation in the phytotelmata studied. Thirteen potential new species were found and two, Hannaella pagnoccae and Hagleromyces aurorensis, were described in this study, it is Hagleromyces a new descriptive genre. The present study showed that the yeast communities were more similar within the same region. The results showed that phytotelmata represent a rich source of new yeast species.